Teoria econômica do crime: a decisão de infringir ou não a Lei - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This work presents the economic theory of crime, a branch elaborated by the economist Gary Becker, which makes it possible to understand human behavior as a rational being that seeks to maximize pleasure and minimize suffering, that is, the individual is considered a rational agent. For that, an opportunity-cost study is used, responding to socioeconomic incentives, from which the benefits and costs resulting from illicit activities are verified. This work aimed to analyze cases of corruption that explain the decision making of the individual who breaks the law, through the economic theory of crime. Thus, it was analyzed, empirically and theoretically, through an economic approach, four cases of corruption that occurred in Brazil, in order to understand whether the behavior of those involved can be considered rational, in view of the socioeconomic, demographic and dissuasion variables that encompasses the gains inherent to acts of corruption, and ways to reduce or eliminate corrupt practices that cause damage to the Brazilian economic system. The methodology was based on a bibliographical review, with a qualitative approach with the description and explanation of the facts, in addition, the study used an exploratory methodology when related to its form of study. Corruption has been a recurrent evil in the national territory, it has eroded the Brazilian public patrimony and becoming an obstacle to the management of the present and the future. In this way, the analysis of the four cases of corruption provided subsidies on individuals taking on criminality, which was based on an individual assessment of the benefits and costs associated with criminal activity, as a consequence of such decisions, corruption causes an aggravation of the economic inequality that favors the emergence of other crimes.
Keywords: Crime; Racional; Corrupção; Econômica; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS